ANALYSIS OF DANGEROUS DRUG CHEMICALS (BKO) CONTENT IN JAMU USING KCKT: A REVIEW STUDY IN VARIOUS AREAS OF INDONESIA - Rochmad Nurchahyo; Amanda Zahira; Aprilia Salwa Maulidina; Elvania Putri; La Ode Akbar Rasydy (RADJA PUBLIKA, 2025)
Abstract The rampant abuse of illegal medicinal chemicals (BKOs) in Indonesian traditional herbal medicine has raised serious concerns, with a recent study using HPLC/HPLC analysis on ten studies revealing the content of hazardous substances such as diclofenac sodium (reaching 297,123 mg/L), dexamethasone (exceeding the safe limit), as well as antalgin and sibutramin HCl in several products in circulation. These findings emphasize the need for strict measures, ranging from strict supervision, public education, to legal action, to protect consumers while ensuring herbal medicine remains a safe and sustainable traditional medicine option for future generations.